ปัจจัยที่มีผลต่อการสื่อสารเรื่องเพศในครอบครัว ของนักเรียนมัธยมศึกษาตอนปลาย ในอำเภอเชียงดาว จังหวัดเชียงใหม่ - รุ่งนภา มหาวรรณศรี (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
Caring factor, noticed factor and parents closeness factor are factor influence family communication on sexual due to these three factors are part of relation creating of parents and teenager. The objectives of this study are to study factor influence family communication on sexual, family communication on sexual, including relation of factor influence family communication on sexual of senior high school students. The subjects in the study included students who are studying in Matthayom 4-6, term 1 in academic year 2015 in Chiang Dow District, Chiang Mai province. There are 3 schools and 285 students. The Data was collected during December 2014 to August 2015. The study instrument was questionnaires and interview that are provided data analysis organization by using descriptive statistics and relational test by using Pearson’s correlation coefficient that was a normality distribution and was confidence level at 95 percent. The study found that factor relation of general information with family communication on sexual found that family format factor, the same sexsual siblings and sex of teenager found that they weren’t related with family communication on sexual (r=-0.005 , 0.011 และ 0.109) which was statistic significance p<000 but when they were considerated of caring factor, noticed factor and parents closeness factor with family communication on sexual found thatcaring factor, noticed factor and closeness factor found that they related with family communication on sexual (r = 0.212 , 0.238 และ 0.197) which was statistic significance as level 0.05. In addition, the results from the interviewas data analysis organization followed issues of consulting, recommendation and discussing about sex between student and parents that was issue about birth control, sexual transmitted disease and behavior when they go to teenager. The results of this study indicated that caring factor, noticed factor and closeness factor were important at family communication on sexual. In consequence, public health personnel and institute concerned should awareness and give precedence to these factors to plan efficiently in promoting and supporting the right family communication on sexual in order to decrease inappropriate sexual behavior of students.